Reviews of recent publications (Studies in 20th & 21st Century Literature, 2007)
Benthien, Claudia and Inge Stephan, eds. Meisterwerke: Deutschsprachige Autorinnen im 20 Jahrhundert Reviewed by Barbara Kosta Finney, Gail, ed. Visual Culture in Twentieth-Century Germany: Text as Spectacle Reviewed by Hester Baer Gigliotti, Simone and Berel Lang, eds. The Holocaust: A Reader Reviewed by Erin McGlothlin Matejka, Ladislav and Krystyna Pomorska, eds. Readings in Russian Poetics: Formalist and Structuralist Views Reviewed by Peter Steiner Rigaud-Drayton, Margaret. Henri Michaux: Poetry, Painting, and the Universal Sign Reviewed by Claire Nodot-Kaufman Van Cauwelaert, Didier. One Way: A Novel Reviewed by Amy L. Hubbell
Keywords: Claudia Benthien; Inge Stephan; Meisterwerke: Deutschsprachige Autorinnen im 20 Jahrhundert; Barbara Kosta; Gail Finney; Visual Culture in Twentieth-Century Germany: Text as Spectacle; Hester Baer; Simone Gigliotti; Berel Lang; The Holocaust: A Reader; Erin McGlothlin; Ladislav Matejka; Krystyna Pomorska; Readings in Russian Poetics: Formalist and Structuralist Views; Peter Steiner; Margaret Rigaud-Drayton; Henri Michaux: Poetry Painting and the Universal Sign; Claire Nodot-Kaufman; Didier Van Cauwelaert; One Way: A Novel; Amy L. Hubbell